Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/cmdc.201000520
|View full text |Cite
|
Sign up to set email alerts
|

Aurones as Modulators of ABCG2 and ABCB1: Synthesis and Structure–Activity Relationships

Abstract: The ability of aurones to modulate the efflux activities of ABCG2 and ABCB1 was investigated by quantifying their effects on the accumulation of pheophorbide A (PhA) in ABCG2-overexpressing MDA-MB-231/R cells and calcein AM in ABCB1-overexpressing MDCKII/MDR1 cells. Key structural features for interactions at both ABCG2 and ABCB1 are a methoxylated ring A, an intact exocyclic double bond, and the location of the carbonyl bond on ring C. Modifications on rings B and C were less critical and served primarily to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…A more detailed structure-activity relationship study further confirmed the potential of the aurone template as a lead for developing potent non-toxic modulators of ABCG2 and ABCB1 [21]. Notably, we identified several methoxylated aurones and related analogs that were equipotent to FTC, an established ABCG2 inhibitor, in reducing the efflux of pheophorbide A (PhA, an ABCG2 substrate) in ABCG2 over-expressing human breast cancer cells (MDA-MB-231/R).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…A more detailed structure-activity relationship study further confirmed the potential of the aurone template as a lead for developing potent non-toxic modulators of ABCG2 and ABCB1 [21]. Notably, we identified several methoxylated aurones and related analogs that were equipotent to FTC, an established ABCG2 inhibitor, in reducing the efflux of pheophorbide A (PhA, an ABCG2 substrate) in ABCG2 over-expressing human breast cancer cells (MDA-MB-231/R).…”
Section: Introductionsupporting
confidence: 60%
“…Cells were sub-cultured when they reached 80-90% confluency and used within 10 passages for assays. The syntheses and purification (to at least 95% purity) of the compounds investigated in this study (Table 1) have been reported by the authors [21]. Their systematic nomenclatures are given in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…14 Probably due to their scarce occurrence in nature, aurones have not been extensively studied for their biological activities although this is rapidly changing. Natural and synthetic aurones have been shown so far to possess a broad spectrum of bioactivity including anticancer, 15 antiparasitic 18,19 and neuroprotective. 20 Some aurone analogues have been recently identified by Manjulatha et al as SIRT1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Because some of the aurone analogs have unique chemical reactivities 24) and show anticancer or neuroprotective activity in cells or in in vivo studies, [25][26][27] we were interested in the relationship between its HDAC inhibitory activity and its biological effects (Fig. 1D).…”
Section: )mentioning
confidence: 99%
“…[25][26][27] Although we think that HDAC is not the molecular target of compound 7, it has been reported that compound 7 inhibits aurora kinase.…”
Section: )mentioning
confidence: 99%